Epidemic Orientalism : Race, Capital, and the Governance of Infectious Disease. - White, Alexandre I. R. (Redwood City : Stanford University Press, 2023)
No detailed description available for "Epidemic Orientalism".
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Preface -- Acknowledgments -- Introduction -- 1. Epidemic Orientalism -- 2. The International Sanitary Conventions at a Colonial Scale -- 3. Epidemics Under the WHO -- 4. The Battle to Police Disease -- 5. Epidemics, Power, and the Global Management of Disease Risk -- 6. Pricing Pandemics -- Conclusion -- Notes -- Index -- Back Cover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Epidemics-Prevention-International cooperation-History.; Communicable diseases-Prevention-International cooperation-History.; Electronic books